Patient Safety at RSGMP Unimus based on Sistem Nasional Akreditasi Rumah Sakit (SNARS) 1.1 Komisi Akreditasi Rumah Sakit - Nurhidayah, Amalia; Sumarwanto, Edi; Arti, Dwi Windu Kinanti (University of Muhammadiyah Semarang, 2022)
Hospitals have an obligation to fulfil the patient’s right to obtain their safety and security while being treated in a hospital as a health service institution for the public. Patient Safety for the patient is a system that makes patient’s treatment safer, including risk assessment, identification and management of patient risk, analysis and reporting of incidents, competency to learn from follow-up incidents and implementation of solutions to minimize the risk and prevent injuries that caused by errors due a treatment. Patient Safety must be considered especially during the period of education, therefore RSGMP Unimus as a learning institution for health service organizers must be considered in this regard. The objective of this study is to measure the readiness of patient safety policies at the Dental and Oral Hospital, Muhammadiyah University, Semarang. This type of research is descriptive and quantitative by using a cross-sectional research design with the Focus Group Discussion technique. Based on the Sistem Nasional Akreditasi Rumah Sakit 1.1 questionnaire by the Komisi Akreditasi Rumah Sakit (KARS), RSGMP Unimus get a fairly good score and partially completed accreditation requirements for aspects of the assessment of Patient Safety Goals (SKP) and Integration of Health Education and Hospital Services (IPKP). Achievement of Patient Safety Goals and Integration of Health Education and Hospital Services at RSGMP Unimus based on the Standard Nasional Akreditasi Rumah Sakit (SNARS) 1.1 which was carried out with the Elemental Assessment of the Patient Safety Goals and Integration of Health Education and Hospital Services standard are partially completed from the SNARS 1.1 assessment with a score of 74.2% and 63.2% which indicates that RSGMP Unimus can make improvements to pass.